Large-scale identification of human bone remains via SNP microarray analysis with reference SNP database. (July 2020) - Cho, Sohee; Kim, Moon-Young; Lee, Ji Hyun; Lee, Hwan Young; Lee, Soong Deok
Highlights: Improved identification of bone remains was achieved by combining high-throughput SNP typing with conventional genetic analysis. Advantages of SNP analysis were presented in terms of typing performance in degraded samples and resolution of ambiguous STR results. Kinship analysis of SNP data using a software program was efficient in large-scale forensic identification. SNPs can be used as complementary markers in large-scale DNA analysis for further investigation. Abstract: Single nucleotide polymorphisms (SNPs) are valuable markers complementary to conventional forensic short tandem repeat (STR) markers in genetic typing, with potential advantages in challenging forensic casework. With the advent of high-throughput technologies, such as microarrays and massively parallel sequencing, the use of SNP typing has now expanded to large-scale forensic applications. Herein, a forensic case is presented to demonstrate the usefulness of SNP typing in identifying large-scale human bone remains with reference database construction. A total of 402 bone remains were recovered from an island in the Jeju Province of Korea where a massive disaster occurred in 1948. The first phase of the identification process was accomplished via conventional DNA typing methods including autosomal and Y-chromosomal STR typing, and mitochondrial DNA sequencing, which resulted in the identification of 74 of 402 remains. The second phase of the identification involved the remaining 327 unidentified remains using SNP typing as a supplementary tool based on Affymetrix resequencing array. The SNP markers of 782 family members were also analyzed and a reference database was constructed for comparison. An additional 51 bone remains were identified in the second phase. SNP data obtained from the supplementary genotyping yielded additional genetic information as well as contributed to kinship testing to determine the second degrees of relationship. In addition SNPs are useful in discriminating ambiguous relationship when only STR data are available. A software program developed for SNP typing system enabled efficient kinship analysis for large-scale forensic identification. The results and the casework are described and discussed.